Determining the delay factors for reconstructed mega-project’s phases and the associated challenges / Basem Adnan Al Khatib - Basem Adnan , Al Khatib (2021)
In recent decades, the construction industry has developed rapidly. Delays in construction projects are a common phenomenon throughout industry. It was and remains one of the most important challenges negatively affecting not only this industry but also the economy. Many studies were conducted to identify the delay factors in new construction projects in different regions, but very few have focused on finding an explanation for the delay causes in reconstruction projects. The study aims to conduct a comprehensive analysis of the delay factors in mega reconstruction projects which took place recently in the Middle East, namely Mataf Expansion Project in Mecca, Saudi Arabia. This project consists of two main parts, nonhistorical and historical and it clarifies the difficulties facing this type of reconstruction projects, which combine demolition and construction works at the same time while the project is under operation. In order to achieve the study goal, twenty-nine interviews were held with the experts working on the project to identify the delay factors and ninety-three questionnaires were distributed by hand to sort them. The results showed that these factors could be divided into three groups: the first one is related to the demolition phase and the second is related to construction phase, while the last is related to overall reconstruction duration. In addition, it has been observed that the materials challenges are considered the major delay factor in the historical building of this project. The questionnaire results were analyzed and delay factors were sorted in a descending order according to the relative importance index (RII). The three main factors affecting the overall reconstruction project duration were site conditions and constraints, electrical and mechanical rerouting works, and design constructability and modification. Finally, recommendations were provided to bridge or reduce the negative impacts of the delay factors in future reconstruction projects.